Evaluasi Kesesuaian Lahan Tanaman Padi Sawah di Desa Weninggalih, Kecamatan Jonggol, Kabupaten Bogor - Ariyanti, Oktavia; Setiawan, Cahyadi; A'Rachman, Fauzi Ramadhoan (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2022)
The need for rice is certainly increasing along with the increase in the population of a region. Weninggalih is one of the villages in Bogor Regency where most of the land cover (63%) is rice fields. The land can only be harvested once a year. So that the area of ​​rice fields is not proportional to the results of rice production produced. These problems raise the interest of researchers in conducting land evaluation analysis on lowland rice plants. The data used comes from the results of data collection with observation techniques and literature study. The sample used was 35 units based on the matching analysis technique to produce an evaluation analysis of lowland rice plants. The matching results show that there are two land suitability classes including marginally suitable (S3) and not suitable (N). As much as 254.20 ha (82.17%) is a marginal suitability class (S3), while 55.20 ha (17.82%) is not suitable (N). The results of the analysis are limited by several factors, including water availability, drainage, soil CEC, base saturation, soil pH, organic C, total N, P2O5, K2O, slope, erosion hazard, inundation height, duration of inundation, and rocks on the surface. After making improvements to the actual land, 309.72 ha became a potential class with a very suitable land suitability class (S1).